Crashworthiness of recycled cardboard panels reinforced with hybrid columnar aluminum tube‐GFRP rods. Issue 11 (24th April 2019) - Fortin, Gabriel Y.; Elbadry, Elsayed A.; Hamada, Hiroyuki
Abstract: This article presents an experimental study on the crushing properties of recycled cardboard panels reinforced with hybrid columnar aluminum tube‐GFRP rods made by a tubular braiding method under quasi‐static compression. The effects of number of hybrid columnar aluminum tube‐GFRP rods with a taper are investigated in single‐layer cardboard panels and two‐layer panels including a thin aluminum interlayer. The results show that GFRP rods with a tapered end display much better progressive crushing behavior with larger specific energy absorption (SEA) compared with rods without a taper, with average values of 65 and 43 kJ/kg, respectively. Moreover, aluminum tubes show a concertina mode of crushing due to folding of the tube walls, with an average SEA of 89 kJ/kg. On the other hand, the highest SEA of 102 kJ/kg is obtained in hybrid columnar aluminum tube‐GFRP rods with a taper, due to interactions of the aluminum on the crushing behavior of the rods. No interactions are observed on the crushing behavior of hybrid columnar structures in cardboard; however, the cardboard does constrain the fiber splaying process of GFRP rods. The interlayer aluminum has a pronounced effect on crushing stability of GFRP rods and hybrid columnar aluminum tube‐GFRP rod reinforced two‐layer cardboard panels.